High-Dose Atorvastatin Reloading Before Percutaneous Coronary Intervention Increased Circulating Endothelial Progenitor Cells and Reduced Inflammatory Cytokine Expression During the Perioperative Period. (May 2014) - Ye, Honghua; He, Fuwei; Fei, Xiaohong; Lou, Yanru; Wang, Shiqi; Yang, Rui; Hu, Yewen; Chen, Xiaomin
Objective: We investigated atorvastatin reloading effects on endothelial progenitor cell (EPC) count and inflammatory cytokine expression after percutaneous coronary intervention (PCI) in patients with stable angina pectoris who had previously received long-term statin treatments. Methods: Patients with stable angina pectoris were treated with 80 mg atorvastatin 12 hours and 40 mg atorvastatin 2 hours before coronary angioplasty (n = 15) or preoperatively with 40 mg/d atorvastatin for 7 days (n = 15) or did not receive atorvastatin (n = 15). CD45−/133+/34+, CD45−/CD34+/kinase insert domain receptor (KDR)+, and CD45−/CD144+/KDR+ EPCs in the peripheral blood were determined by flow cytometry 1 hour before as well as 1 hour, 6 hours, and 24 hours after PCI. Soluble intercellular adhesion molecule 1 (sICAM-1), hypersensitive C-reactive protein (hCRP), and troponin-I (TnI) serum concentrations were analyzed immediately prior to and 24 hours after PCI. Results: In the 40mg Atorvastatin and control groups, none of the analyzed EPC blood concentrations changed significantly from 1h before operation to 1h and 6 h postoperative values. In contrast, the number of circulating early differentiation stage EPCs CD45-/133+/34+ and CD45-/CD34+/ KDR+ raised significantly from 1 h preoperative values (57.3±9.3; 57.3 ± 10.7) to 1 h postoperative ((74.4 ± 11.4; 78.8 ± 16.2), (p < 0.05)) and 6 h postoperative ((93 ± 16.9; 99.7 ± 11.9), (p < 0.05)) concentrations after coronary angioplasty in the 80mg Atorvastatin medication patients. In the control group, the sICAM-1 (174.55 ± 38.91 vs 204.11 ± 58.24) and hCRP (1.89 ± 1.93 vs 9.0 ± 11.1) serum concentrations at 24 hours after PCI were significantly elevated ( P < .05) compared to preoperative values, whereas the increases in the 2 groups treated with atorvastatin were not significant. In addition, the rise in serum TnI concentration level from pre- to postoperative in the 80-mg (0.02 ± 0.02 vs 0.09 ± 0.08) and the 40-mg (0.01 ± 0.03 vs 1.2 ± 2.59) reloading groups was less than that of the controls (0.01 ± 0.02 vs 1.75 ± 3.09) (p < 0.05). Conclusion: Our results suggested that high-dose atorvastatin application before PCI triggered early EPC circulation. Furthermore, postoperative inflammatory cytokine sICAM-1 as well as hCRP serum levels were reduced, while postinterventional myocardial injury marker TnI elevations were inversely correlated with statin reloadings.